A systematic mapping literature review of education around sexual and gender diversities - López-Orozco, Christian Fernando; López-Caudana, Edgar Omar; Ponce, Pedro (Frontiers in Sociology, 2022)
Education around sexual and gender identities is highly important to understand diversity and prevent discrimination, violence, and even murder. Nevertheless, educational institutions around the world are lacking a curriculum that explicitly includes diversity and acknowledges the LGBTQ+ community, a minority that over the years has been facing consequences from this exclusion. This study presents a detailed description of the process applied to analyze the studies using a systematic mapping literature review, as well as the positive results found from those educational institutions that started their path to inclusion around sexual and gender diversities through their curricula. The research questions targeted in this work are: What is being taught in educational institutions regarding sexual and gender diversities? What are the approaches used inside the classrooms to teach sexual and gender diversities? Which students are receiving education regarding sexual and gender diversities? Is there a technological approach and/or tool used to teach sexual and gender diversities? After applying the filtering processes, 69 studies were selected from five different online libraries: ACM, DOAJ, Lens.org, SCOPUS, and SpringerLink. The conclusions made from the findings of this review are that those studies that do tackle concerns around the topic have proven to benefit the LGBTQ+ community, the education around sexual and gender diversities predominates within the healthcare field, there are a lack of studies around this topic in Latin American countries, and technological tools are minimally used during the teaching processes.